Book Reviews. (1st August 2014) - ,
Abstract : Book Reviews Theresa Morris, Hans Jonas's Ethic of Responsibility: From Ontology to Ecology (Lewis Coyne) Peter H. Kahn and Patricia H. Hasbach (eds.), Ecopsychology: Science, Totems, and the Technological Species (Alan E. Stewart) Louise Westling, The Logos of the Living World: Merleau-Ponty, Animals, and Language (Brian Onishi) A. James Wohlpart, Walking in the Land of Many Gods: Remembering Sacred Reason in Contemporary Environmental Literature (Daniel Crescenzo) Peggy F. Bartlett and Geoffrey W. Chase (eds.), Sustainability in Higher Education: Stories and Strategies for Transformation (John Blewitt)